2008
DOI: 10.1039/b811726h
|View full text |Cite
|
Sign up to set email alerts
|

Target-selective photo-degradation of HIV-1 protease by a fullerene-sugar hybrid

Abstract: A designed fullerene-sugar hybrid effectively and selectively degraded the target protein, HIV-1 protease, which has high affinity for the fullerene moiety; degradation was achieved using long-wavelength UV or visible photo-irradiation, in the absence of any additives and under neutral conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 23 publications
0
37
2
Order By: Relevance
“…Therefore, our data definitively demonstrate that fullerene derivatives fail to inhibit HIV-1 protease at doses that potently block HIV-1 maturation. These results conclusively show that fullerenes 1 and 2 are strongly anti-HIV active, but not via HIV-1 protease, contradicting the multiple studies previously reported (11,13,(18)(19)(20)(21)35).…”
Section: Characterization Of the Early Steps Of The Viral Life Cycle contrasting
confidence: 81%
See 3 more Smart Citations
“…Therefore, our data definitively demonstrate that fullerene derivatives fail to inhibit HIV-1 protease at doses that potently block HIV-1 maturation. These results conclusively show that fullerenes 1 and 2 are strongly anti-HIV active, but not via HIV-1 protease, contradicting the multiple studies previously reported (11,13,(18)(19)(20)(21)35).…”
Section: Characterization Of the Early Steps Of The Viral Life Cycle contrasting
confidence: 81%
“…Our data have corroborated the reported anti-HIV-1 activity of compounds 1 and 2 but do not support findings or predictions indicating reverse transcriptase (16) or protease (11,13,(18)(19)(20)(21)35) as their targets. Instead, we have demonstrated for the first time that fullerene inhibitors block HIV-1 maturation.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The number of studies has steadily grown covering fundamental to applied fields of science and technology of fullerene chemistry. [1][2][3][4][5] Thus, C 60 and C 60 -based nanomaterials have been contributing to a variety of promising applications to protease inhibitors 6,7) , antibacterial 8) and anticancer 9) drugs in medicine, high surface area particles and supports in catalysis 10) , electron carriers in electronic devices 1) , and semiconductors in solar cells [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%